KEANEKARAGAMAN JENIS RAYAP PADA LAHAN AGROFORESTRI DAN KEBUN KEMIRI DI DESA BAKUBAKULU KECAMATAN PALOLO KABUPATEN SIGI - Abdul Hapid; Zulkaidhah Zulkaidhah (Biocelebes, 2019)
Termites play important roles in organic matter decomposition, nutrient cycling, and soil structure in tropical rain forests. When forests are replaced by agriculture, termite species richness, abundance, and function often decline. This research was aimed to determine diversity and composition of termites in three land use types (kemiri gardens, simple and complex agroforestry). Methods of sample collection using transects with a size of about 2 x 100 m, divided into 20 sections (2 x 5 m). The collected samples were collected for identification purposes. Variables measured the diversity of termites which includes the type and number of species (species richness) found in each land use. Diversity and abundance of species of termites were analyzed using the Shannon Diversity IndexWienner. The results showed that the total number of termite species founded in all area was 6 species comprising 2 families, i.e. termitidae and rhinotermitidae. Alpha diversity of termite founded in kemiri gardens was 4 species, and 5 species founded in complex agroforestry and 3 species founded in simple agroforestry. The highest frequency of termite species was 0,5 that achieved by Odontotermes sp in kemiri gardens and simple agroforestry, while the lowest frequency was 0,05 that achieved by Schedorhinotermes sp. in candlenut gardens. Further, the Shannon species diversity Index (H’) of each land use types were 0,93, 0,95 and 1,47 in simple agroforestry, kemiri gardens and complex agroforestry, respectively.